Agricultural growth trends and outlook for Southern Africa - Chilonda, Pius; Musaba, Emmanuel; Zikhali, Precious (International Food Policy Research Institute, 2010)
The Southern African Development Community (SADC) countries, along with other African countries, have recognized and prioritized the agriculture sector as key to overall economic growth, poverty reduction, and enhancing food security and have accordingly committed themselves to implement several regionally, continentally and internationally shared targets or goals. These include the Comprehensive African Agriculture Development Program (CAADP), the SADC Regional Indicative Strategic Development Plan (RISDP) and the Millennium Development Goals (MDGs). Under CAADP, put together by the African Union's New Economic Partnership for Africa's Development (AU/NEPAD) and signed by African states in 2003, African governments committed to achieving annual agricultural growth of at least 6%. In order to ensure that sufficient resources were made available for the CAADP implementation, countries signed the AU Maputo Declaration in 2003 in which they agreed to increase national budgetary resources to the agriculture sector to at least 10% of their respective national budgets by 2008. The principle behind CAADP is to use agriculture-led growth to achieve the first MDG of halving poverty and hunger by 2015, a goal that is also set by SADC RISDP.